2018
DOI: 10.1111/scs.12643
|View full text |Cite
|
Sign up to set email alerts
|

Parents caring for children with normal life span threatening disabilities: a narrative review of literature

Abstract: Background Parents caring for children with normal life span threatening disabilities are exposed to numerous and accumulated stressors. In alignment with current approaches of evidence and value based care, it is essential to integrate knowledge of what encourages parents to hold or recover well‐being in care planning and delivery. An omission in knowledge was identified concerning the outline of parents’ challenges and ambitions understood from their perspective. Aim The aim of this study was to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
(458 reference statements)
0
9
0
Order By: Relevance
“…There is minimal evidence on the impact of postural management on family life (Gmelig Meyling et al., 2018), with researchers calling for more qualitative methods to examine the emotional implications of providing highly specialist equipment (Nicolson et al., 2012). The current study identified important new findings regarding carers’ feelings of fear and parents needing to become strong advocates, which may reflect the broader daily challenges in caring for someone with complex neurodisability (Geuze and Goossensen, 2018; Nicholl and Begley, 2012). Indeed, previous research has echoed parental stress for carers of children with physical disabilities, with Egilson (2011) reporting positive support from therapy services but also frustrations including a lack of consideration regarding the family’s needs and a desire for more information from therapists.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…There is minimal evidence on the impact of postural management on family life (Gmelig Meyling et al., 2018), with researchers calling for more qualitative methods to examine the emotional implications of providing highly specialist equipment (Nicolson et al., 2012). The current study identified important new findings regarding carers’ feelings of fear and parents needing to become strong advocates, which may reflect the broader daily challenges in caring for someone with complex neurodisability (Geuze and Goossensen, 2018; Nicholl and Begley, 2012). Indeed, previous research has echoed parental stress for carers of children with physical disabilities, with Egilson (2011) reporting positive support from therapy services but also frustrations including a lack of consideration regarding the family’s needs and a desire for more information from therapists.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies identified frustrations such as the bulky and restrictive nature of equipment (Hutton and Coxon, 2011; McDonald et al., 2007). The current participants identified additional frustrating factors including loss of identity, the burden of equipment costs, inadequate focus on prevention and wider accessibility difficulties, reflecting the many challenges faced when living with such complex neurodisability (Geuze and Goossensen, 2018; Nicholl and Begley, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified that parents of children with PIMD often struggle with finding and maintaining a careful balance between the many matters affecting them ( Breitkreuz et al, 2014 ; Geuze & Goossensen, 2019 ; Whiting, 2014 ). Studies have identified impacts on physical and psychological (mental) health and described challenges regarding the loss of free time and social activities, financial difficulties related to reduced income and higher costs, lack of access to professional services and the impacts on care for siblings and the life partner relationship ( Muir & Strnadová, 2014 ; Tadema & Vlaskamp, 2010 ; Woodgate et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also revealed positive experiences, namely, increased closeness in families and communities, increased spirituality, enhanced arrangement of personal resources and a sense of fulfillment for having done everything that could be done for the benefit of the child ( Graungaard, 2007 ; Hastings et al, 2005 ; Luijkx, 2016 ). Research has indicated that the possible implications associated with parenting a child with PIMD are strongly associated with procedures and practices within the healthcare and service systems that impact family life and create collateral stress ( Geuze & Goossensen, 2019 ; Peer & Hillman, 2014 ; Woodgate et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…How will they face an unexpected experience of parenting a child who is different from typical children? Parenting a child with an intellectual disability, such as Down syndrome, poses a challenge to self-identity (Geuze & Goossensen, 2018; Lou et al, 2018; Whiting, 2013, 2014); How the parent embraces or merely adapts to such an identity depends, in part, on whether parents have access to cultural narratives and resources to inform their performance as a parent in ways that are socially understood and personally meaningful (Solomon, 2012; Van Riper, 2007b).…”
Section: Introductionmentioning
confidence: 99%